Problems of agricultural development in Guyana - Muller, G. J. ([s.n.] GeorgetownGY, 1987)
Reviews performance of various agricultural sectors in Guyana between 1977-86. Outlines some agricultural development objectives during this period and alludes to their effects or results. Discusses sectoral problems such as marketing, foreign exchange, resource assessment/management that may affect future development of agriculture in Guyana.